Post-saccadic Eye Movement Indices Under Cognitive Load: A Path Analysis to Determine Visual Performance - Salehi Fadardi, Marzieh; Salehi Fadardi, Javad; Mahjoob, Monireh; Doosti, Hassan (Journal of Ophthalmic and Vision Research, 2022)
Purpose: The evidence on the linear relationship between cognitive load, saccade, fixation, and task performance was uncertain. We tested pathway models for degraded task performance resulting from changes in saccadic and post-saccadic fixation under cognitive load. Methods: Participants’ (n = 38) eye movements were recorded using a post-saccadic discrimination task with and without arithmetic operations to impose cognitive load, validated through recording heart rate variability and subjective measurement. Results: Results showed that cognitive load led to longer latencies of saccade and fixation; more inaccurate responses and fewer secondary saccades (P < 0.001). Longer saccade latencies influenced task performance indirectly via increases in fixation latency, therefore, longer reaction times and higher response errors were observed due to limited fixation duration on desired target. Conclusion: We suggest that latency and duration of fixation indicate efficiency of information processing and can predict the speed and accuracy of task performance under cognitive load.